WORK-RELATED TO TEACHING CORRECT WRITING WAYS OF ORGANIZATION - Khakimov Azizkhan Asrorovich (Galaxy International Interdisciplinary Research Journal, 2023)
Formed based on written speech. correct perception and correct pronunciation of words are one of the most necessary factors of literate writing. According to the information provided by psychologists and methodologists, visual intuition and memorization of what is written play a key role in acquiring writing skills. According to his calculations, he connected the orthographic skill with psycho-physiological nature and paid the main attention to his reading and imagination.